Association between ultra-processed foods frequency of intake and sarcopenia in older adults: a cross-sectional study (Research, Society and Development, 2022)
Ultra-processed foods (UP) are frequently associated with poor diet quality and lack many nutrients necessary for skeletal muscle health, which could contribute to developing sarcopenia. However, investigations about possible associations between the intake of UP and sarcopenia are missing. This study aimed to describe the magnitude of the exposition to UP (eating frequency) and compare it in older adults with and without sarcopenia. It also described associations between the magnitude of exposition of UP with body composition markers of sarcopenia in all subjects. It was a cross-sectional study with a sample of 118 community-dwelling older adults. Body composition was accessed by Dual-energy X-ray absorptiometry (DXA) and UP intake by a food frequency questionnaire (FFQ). All foods in the FFQ were categorized into two groups: (1) non-UP and (2) UP. SCORE I (mean score for food group 1) and SCORE II (mean score for food group 2) were calculated. The eating frequency of UP was near 3 to 4x/week and higher for sarcopenic subjects (p